Relationships between the Theater of the Oppressed and media education at school - Fantin, Mônica (2019)
The text discusses the relationship between education, communication and art in the formation of cultural and media competencies among school students. In the context of a broader research on multiliteracy and media competencies, a master’s research was conducted to understand how students conceive their own culture and the culture of others from Internet search and media productions. Through the approach between media education and the Theater of the Oppressed (TO), a didactic intervention was proposed using the Episodes of Situated Learning (EAS) methodology in eighth-grade young students from a public school in Florianópolis/SC. The power of such articulation promoted educational and cultural experiences that favored other narratives on the process of teaching and learning; revealed other students’ views of themselves, the media, the knowledge and the cultural environment; and fostered collaborative and creative practices in and out of school.